Novel Mutation in a Patient with Cholesterol Ester Storage Disease. (5th February 2015) - Lin, Patrick; Raikar, Sheela; Jimenez, Jennifer; Conard, Katrina; Furuya, Katryn N.
Abstract : Cholesterol ester storage disease (CESD) is a chronic liver disease that typically presents with hepatomegaly. It is characterized by hypercholesterolemia, hypertriglyceridemia, high-density lipoprotein deficiency, and abnormal lipid deposition within multiple organs. It is an autosomal recessive disease that is due to a deficiency in lysosomal acid lipase (LAL) activity, which is coded by the lysosomal acid lipase gene (LIPA). We describe the case of a 5-year-old south Asian female incidentally found to have hepatomegaly, and subsequent workup confirmed the diagnosis of CESD. DNA sequencing confirmed the presence of a novel hepatic mutation. It is a four-nucleotide deletion c.57_60delTGAG in exon 2 of the LIPA gene. This mutation is predicted to result in a premature translation stop downstream of the deletion (p.E20fs) and, therefore, is felt to be a disease-causing mutation.